Social media and student behaviour - Peláez-Verdet, Antonio; Mariscal-García, Marta (My University, 2017)
Social media and student behaviour when searching for a job. The paper focus on the higher education students and their approach when it comes to seek for a job. As a main finding we can mention that, in the early stages of their career, social media are not perceived as a tool that can leverage their efforts to fulfil the employers expectations. Turns out that it changes by the end of the bachelor studies.
Keywords: Redes sociales; Búsqueda de empleo; Social media; Student behaviour